Management of insect pests in vegetable crops : concepts and approaches - Vishwakarma, Ramanuj, 1984-; Kumar, Ranjeet, 1982- (Burlington, ON, Canada ; Palm Bay, Florida, USA : Apple Academic Press, 2020)
"This new book on the sustainable management of insect pests in important vegetables offers valuable management strategies in detail. It focuses on eco-friendly technology and approaches to mitigating the damage causes by insect pests with special reference to newer insecticides. Chapters in Management of Insect Pests in Vegetable Crops: Concepts and Approaches provide an introduction to vegetable entomology and go on to present a plethora of research on sustainable eco-friendly pest management strategies for root vegetables, spice crops, tuber crops, and more. It looks at the damage done by snails, slugs, phytophaous mites of vegetable crops, and more and presents management strategies. Vegetable crops that are infested by several insect pests right from the nursery to the harvesting stage cause enormous crop losses. Given that it is estimated that up to 40 percent of global crops are lost to agricultural pests each year, new research on effective management strategies is vital. The valuable information provided in this book will be very helpful for faculty and advanced-level students, scientists and researchers, policymakers, and others involved in pest management for vegetable crops."--
Eco-Friendly Pest Management Strategies of Root Vegetable Crops / Kalmesh Managanvi, Ramanuj Vishwakarma, and Jaba Jagdish -- Insect Pests of Ginger and Turmeric and Their Management / Budhachandra Thangjam and Navendu Nair -- Insect Pests of Cumin and Their Management / Geetanjly, Rahul Kumar Chandel, Preeti Sharma, and Vijay Kumar Mishra -- Insect Pests of Cucurbitaceous Vegetables Crops / Hari Chand Ingle and Dipak Shyamrao -- Phytophagous Mites of Vegetable Crops and Their Management / Pushpa Singh, R. N. Singh, and C. P. Srivastva -- Mite Problems in Spice Crops and Their Management / Mrinalini Kumari and Dinesh Prasad Gond -- Pesticide Residue in Vegetables / Pritam Ganguli -- Insect Pests of Tomato and Their Management / Atanu Seni -- Insects of Tuber Crops and Their Management / P. Chand, Amit Singh, and R. Vishwakarma -- Problems of Snails and Slugs in Vegetable Crops and Their Management / Ranjeet Kumar.
OCLC-licensed vendor bibliographic record.
Keywords: Vegetables -- Diseases and pests -- Control; Insect pests -- Control; Vegetables -- Diseases and pests -- Control -- Environmental aspects; SCIENCE / General; SCIENCE / Life Sciences / Botany; SCIENCE / Life Sciences / Zoology / Entomology